A Practical Approach to Pharmaceutical Policy - Seiter, Andreas (World Bank, 2012)
This book discusses the wide range of challenges faced by policy makers in the pharmaceutical sector, presents the current know-how in terms of policy measures, and provides specific examples of policy packages that can be used in defined circumstances, even if one assumes a certain degree of political resistance and capacity limits on the side of the implementing agency. This book focuses on developing countries and tries to address the issues faced by both low- and middle-income countries. The book does not cover the vaccines market and its respective policies because too many differences exist between the markets for vaccines and pharmaceuticals to cover both subsectors in one publication of this type. The book ends with an outlook on how things might evolve in the longer term. It assumes that some form of convergence will take place toward "models that work," thus reducing the fragmentation of policies and enhancing regulatory and economic efficiencies over time-one hopes to the benefit of all stakeholders in the sector and, in particular, those who, as patients, currently do not have reliable access to effective and safe medicines.